Islamic Law and Gender Equality: Challenges and Reforms in Sri Lanka’s Muslim Marriage and Divorce Act - Dawood, Shamila (Institut Agama Islam Negeri (IAIN) Pontianak, 2024)
This article examines the ongoing debates and reform efforts surrounding the Muslim Marriage and Divorce Act of 1951 (MMDA) in Sri Lanka. The Act has faced substantial criticism for its inability to adapt to the evolving needs of modern society, often prioritizing men’s interests over women’s rights. Despite numerous reform attempts, reaching a consensus on crucial provisions has proven challenging, creating significant obstacles to amending the MMDA. Employing library research, this article analyzes reports from various committees to assess current practices, which reveal conflicting perspectives between committees and civil society organizations. This study re-evaluates the MMDA’s provisions to determine whether proposed reforms align with Sharia law while meeting international legal standards, particularly Sri Lanka’s obligations to eliminate all forms of discrimination against women, while considering religious and cultural sensitivities. The article underscores the need for collaborative dialogue among stakeholders to foster reforms that address the evolving Muslim community’s legal needs, focusing on justice and equality. [Artikel ini mengkaji perdebatan yang sedang berlangsung dan upaya reformasi seputar Undang-Undang Perkawinan dan Perceraian Muslim tahun 1951 di Sri Lanka. Undang-undang tersebut telah menghadapi kritik besar karena gagal beradaptasi dengan kebutuhan masyarakat modern yang terus berkembang, yang sering kali memprioritaskan kepentingan laki-laki di atas hak-hak perempuan. Meskipun ada banyak upaya reformasi, mencapai konsensus tentang ketentuan-ketentuan utama telah terbukti menantang, menciptakan hambatan signifikan terhadap amandemennya. Dengan menggunakan penelitian kepustakaan, artikel ini menganalisis laporan dari berbagai komite untuk menilai praktik terkini, di mana terdapat pandangan yang saling bertentangan antara komite dan organisasi masyarakat sipil. Studi ini mengevaluasi kembali ketentuan-ketentuan tersebut untuk menilai apakah reformasi yang diusulkan selaras dengan hukum Syariah sekaligus memenuhi standar hukum internasional, khususnya kewajiban Sri Lanka untuk menghapuskan segala bentuk diskriminasi terhadap perempuan, sambil mempertimbangkan kepekaan agama dan budaya. Artikel ini menggarisbawahi perlunya dialog kolaboratif di antara para pemangku kepentingan untuk mendorong reformasi yang memenuhi kebutuhan hukum komunitas Muslim yang terus berkembang dengan menekankan keadilan dan kesetaraan.]